Penerapan Team Game Tournament Untuk Meningkatkan Keaktifan Siswa Dalam Layanan Bimbingan Klasikal - Afrina Rosada; Yuanita Dwi Krisphianti; Ida Kusumawati (Jurnal Pendidikan Sosial Dan Konseling, 2025)
Student activity is an important aspect in classical guidance services, because it reflects the emotional and social involvement of students. However, in practice, students often remain passive during the service. This research aims to increase student activity through the application of the Team Games Tournament (TGT) method in classical guidance services. The research method used is Classroom Action Research (PTK) with one cycle involving the stages of planning, implementation, observation and reflection. The research results showed a significant increase in student activity: before the action only 1 student (2.63%) was classified as active, whereas after the implementation of TGT, as many as 34 students (89.47%) were classified as active. Discussion activities, courage to express opinions, and student reflection on the material have increased. In conclusion, the application of the TGT method has proven to be effective in increasing student activity and can be an innovative alternative strategy in implementing classical guidance services.